Implementation of tobacco cessation brief intervention in complementary and alternative medicine practice: qualitative evaluation - Emery R. Eaves; Amy Howerter; Mark Nichter; Lysbeth Floden; Judith S. Gordon; Cheryl Ritenbaugh; Myra L. Muramoto (BMC, 2017)
Abstract Background This article presents findings from qualitative interviews conducted as part of a research study that trained Acupuncture, Massage, and Chiropractic practitioners' in Arizona, US, to implement evidence-based tobacco cessation brief interventions (BI) in their routine practice. The qualitative phase of the overall study aimed to assess: the impact of tailored training in evidence-based tobacco cessation BI on complementary and alternative medicine (CAM) practitioners' knowledge and willingness to implement BIs in their routine practice; and their patients' responses to cessation intervention in CAM context. Methods To evaluate the implementation of skills learned from a tailored training program, we conducted semi-structured qualitative interviews with 54 CAM practitioners in Southern Arizona and 38 of their patients. Interview questions focused on reactions to the implementation of tobacco cessation BIs in CAM practice. Results After participating in a tailored BI training, CAM practitioners reported increased confidence, knowledge, and motivation to address tobacco in their routine practice. Patients were open to being approached by CAM practitioners about tobacco use and viewed BIs as an expected part of wellness care. Conclusions Tailored training motivated CAM practitioners in this study to implement evidence-based tobacco cessation BIs in their routine practice. Results suggest that CAM practitioners can be a valuable point of contact and should be included in tobacco cessation efforts.